Uncovering dispersion properties in semiconductor waveguides to study photon-pair generation. (23rd September 2016) - Laiho, K; Pressl, B; Schlager, A; Suchomel, H; Kamp, M; Höfling, S; Schneider, C; Weihs, G
Abstract: We investigate the dispersion properties of ridge Bragg-reflection waveguides to deduce their phasematching characteristics. These are crucial for exploiting them as sources of parametric down-conversion (PDC). In order to estimate the phasematching bandwidth we first determine the group refractive indices of the interacting modes via Fabry–Perot experiments in two distant wavelength regions. Second, by measuring the spectra of the emitted PDC photons, we gain access to their group index dispersion. Our results offer a simple approach for determining the PDC process parameters in the spectral domain, and provide important feedback for designing such sources, especially in the broadband case.